REPercussions: how geminiviruses recruit host factors for replication - Shakir, Sara; Mubin, Muhammad; Nahid, Nazia; Serfraz, Saad; Qureshi, Muhammad Amir; Lee, Taek-Kyun; Liaqat, Iram; Lee, Sukchan; Nawaz-ul-Rehman, Muhammad Shah (Frontiers in Microbiology, 2023)
Circular single-stranded DNA viruses of family Geminiviridae encode replication-associated protein (Rep), which is a multifunctional protein involved in virus DNA replication, transcription of virus genes and suppression of host defense responses. Geminivirus genomes are replicated through the interaction between virus Rep and several host proteins. The Rep also interacts with itself and virus replication enhancer protein (REn), which is another essential component of the geminivirus replicase complex that interacts with host DNA polymerases α and δ. Recent studies revealed the structural and functional complexities of geminivirus Rep, which is believed to have evolved from plasmids containing a signature domain (HUH) for single-stranded DNA binding with nuclease activity. The Rep coding sequence encompasses the entire coding sequence for AC4, which is intricately embedded within it, and performs several overlapping functions like Rep, supporting virus infection. This review investigates the structural and functional diversity of the geminivirus Rep.